Social media in undergraduate teaching and learning: A scoping review protocol. - Richard Hayman; Erika E Smith (PLoS ONE)
Objective To conduct a scoping review that systematically examines the body of research on social media in undergraduate teaching and learning in order to identify key issues, trends, gaps, and needs. Our objectives include determining what methods have been commonly used to study social media in undergraduate teaching and learning, and to synthesise insights from published research findings within the fields of higher education, educational technology, and the scholarship of teaching and learning. Introduction The use of social media technologies in post-secondary environments has been increasing over time, and especially following the shift to remote teaching and learning during the COVID-19 pandemic, this growth has continued. This review addresses a need to analyse and understand the body of research on the use of social media across undergraduate contexts for teaching and learning. Inclusion criteria This scoping review includes peer-reviewed journal articles on social media in an undergraduate teaching or learning context published at any time, in English. In addition to including concepts and terms related to social media broadly, based on global social media usage, we include within our search the most commonly used social media platforms. We excluded items from the grey literature (such as reports, dissertations, and theses), and studies that focus on groups outside of the undergraduate population of interest (e.g., in elementary, secondary, or graduate settings, etc.). Methods Systematic searching will be conducted in relevant subject and multidisciplinary databases: Education Database, Education Research Complete, ERIC, British Education Index, Australian Education Index, Academic Search Complete, and Scopus. Records will be deduplicated and screened using Covidence software, with each record independently reviewed by two researchers in both rounds, screening titles and abstracts in the first round, and full-text of articles in the second. Researchers will meet to discuss discrepancies and make decisions using a consensus model, and a third researcher will be independently tasked with resolving any conflicts. Data extraction will also use two independent researchers to review each article.